Studies in symbolic interaction. - Denzin, Norman K. (Studies in symbolic interaction,, 2010)
The essays in this bi-annual series consist of original research and theory within the general sociological perspective known as symbolic interactionism. Longer than conventional journal-length articles, the essays wed mico and macro concerns within a qualitative, ethnographic, autoethnographic and performance studies orientation. International in scope, the series draws upon the work of urban ethnographers, interpretive, constructionist, ethnomethodological, critical race, postcolonial, feminist, queer, and cultural studies traditions.